Designing a vehicle driving simulator: algorithm and programming - Nguyễn Bá Hải; Phan Ngọc Trung (Journal of Technical Education Science, 2012)
This paper presents a PID controller for artificially producing steering feel in driving simulators and designs simulators’ 3D simulation of virtual environment. The novel contributions of this research are the 3D environments including sounds, movement of cars, collision detections and algorithm for connecting 3D environment to peripheral equipments. This research has been tested with experimental results. When the 3D driving simulator is produced in Vietnam it offers a low-cost solution to driving training, reduction of fuel and the possibility of replacement of imported products